Intimate partner violence, circulating glucose, and non-communicable Disease: Adding insult to injury? - Abigail Weitzman; Bridget J. Goosby (Elsevier, 2021)
Analyzing data from the 2015-2016 Indian Demographic and Health Survey (N = 41,768), we investigate how women's circulating glucose varies with the severity of intimate partner violence (IPV) they have experienced in the last year and how their likelihoods of corresponding noncommunicable diseases vary with IPV severity in their lifetime. Consistent with a physiological stress response, women who have recently experienced severe IPV exhibit higher glucose levels and are more likely to have extremely high levels-forewarning of disease development-than women who have not experienced IPV. Correspondingly, women who have ever experienced severe IPV in their lifetime have 33%-200% higher probabilities of diabetes, heart disease, thyroid disorders, and cancer and are 70% more likely to have any of these diseases and 175% more likely to have multiple than women who have experienced none.